2014
DOI: 10.1080/17470919.2014.931885
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of stable dominance interactions in prairie vole peers: Relationships with alcohol drinking and activation of the paraventricular nucleus of the hypothalamus

Abstract: Dominance hierarchies are an important aspect of group-living as they determine individual access to resources. The existence of dominance ranks in access to space has not been described in socially monogamous, communally nesting prairie voles (Microtus ochrogaster). Here we tested whether dominance could be assessed using the tube test. We also tested whether dominance related to alcohol intake, similar to what has been demonstrated in non-monogamous species. Same-sex pairs of unfamiliar peers were tested in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…Following CSC stress, submissive mice voluntarily consume more alcohol compared to either singly-housed controls ( Bahi, 2013 ; Peters et al, 2013 ) or dominant males ( Hilakivi-Clarke and Lister, 1992 ). Similar findings are reported using CSC protocols in rats ( Blanchard et al 1987 , 1992 ; Ellison, 1987 ), in evaluations of social dominance among prairie voles ( Anacker et al, 2014 ), and in socially housed squirrel monkeys ( McKenzie-Quirk and Miczek, 2008 ); likewise, social dominance appears to have a protective effect against escalated alcohol intake in cynomolgus monkeys ( Helms et al, 2012 ; Jimenez and Grant, 2017 ). In rats, pre-stress alcohol intake does not correlate with later hierarchical standing or drinking following CSC stress, indicating that elevated drinking likely results from subordination stress rather than individual differences in alcohol preference ( Blanchard et al, 1992 ; Hilakivi-Clarke and Lister, 1992 , but Wolffgramm and Heyne, 1991 ).…”
Section: Animal Models Of Social Stress and Pathological Patterns Of supporting
confidence: 77%
“…Following CSC stress, submissive mice voluntarily consume more alcohol compared to either singly-housed controls ( Bahi, 2013 ; Peters et al, 2013 ) or dominant males ( Hilakivi-Clarke and Lister, 1992 ). Similar findings are reported using CSC protocols in rats ( Blanchard et al 1987 , 1992 ; Ellison, 1987 ), in evaluations of social dominance among prairie voles ( Anacker et al, 2014 ), and in socially housed squirrel monkeys ( McKenzie-Quirk and Miczek, 2008 ); likewise, social dominance appears to have a protective effect against escalated alcohol intake in cynomolgus monkeys ( Helms et al, 2012 ; Jimenez and Grant, 2017 ). In rats, pre-stress alcohol intake does not correlate with later hierarchical standing or drinking following CSC stress, indicating that elevated drinking likely results from subordination stress rather than individual differences in alcohol preference ( Blanchard et al, 1992 ; Hilakivi-Clarke and Lister, 1992 , but Wolffgramm and Heyne, 1991 ).…”
Section: Animal Models Of Social Stress and Pathological Patterns Of supporting
confidence: 77%
“…Connectivity between PVN–RSC–BLA may be related to an association of a spatial context with a socially salient stimuli. While OXT projections from PVN may probably influence the regulation of social salience in the whole network ( Johnson et al, 2017 ), it is also reported to be sensitive to external stimuli ( Anacker et al, 2014 ; Liu et al, 2001 ) that can impact OXT synthesis and release ( Smith and Wang, 2014 ). The BLA may act as an associative site for stimulus-outcome representations ( Cardinal et al, 2002 ), which would allow an appropriate response according to previous social encounters, information that possibly requires hippocampus-associated memory (BLA-DG) ( Frey et al, 2001 ; Tashiro et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…While acute increases in glucocorticoids can promote aggression [67], chronic glucocorticoid exposure tends to suppress aggression and increase social avoidance [68,69]. Chronically elevated glucocorticoids can also impair the formation and maintenance of social bonds by reducing the expression of affiliative behaviours central to these bonds [68,70]. Differences in the behavioural effects of glucocorticoids across timescales of exposure probably stem, at least in part, from the cumulative effects of glucocorticoid exposure on other signalling systems.…”
Section: Steroid Hormones and Social Plasticitymentioning
confidence: 99%